Dampak Pelanggaran Etika Bisnis terhadap Konsumen: Studi Kasus Promotor Mecimapro dalam Penyelenggaraan Konser Musik Internasional di Indonesia - Salsha Dwi Agustien; Halimah Zahrah; Maisya Hayina Zahra; Ghina Aulia Asy Syifa; Rahma Khairunnisa Amalia (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The growth of the international music concert industry in Indonesia has led to the emergence of specialized promoters such as PT Melania Citra Permata (Mecimapro). Since 2015, Mecimapro has actively organized concerts featuring South Korean artists, yet its business practices have often drawn criticism for ethical violations. This study aims to examine the ethical breaches committed by Mecimapro and their impact on consumer rights and trust. The research method used is a literature review, employing the ethical business theory of Keraf and the stakeholder theory of Freeman. The findings reveal violations of principles such as honesty, fairness, autonomy, and moral integrity in various concerts, including unilateral venue changes, inadequate facilities, and delayed refund processes. These violations have a systemic impact on consumer safety, comfort, and perception, potentially tarnishing Indonesia's entertainment industry's reputation on a global scale. The study highlights the urgency of implementing ethical principles and accountability in entertainment business practices to ensure consumer protection and industry sustainability.